‘‘La preescritura en los niños de subnivel inicial 2 de la unidad educativa Belisario Quevedo’’ - Herrera Naranjo, Carla Tatiana (2023)
The research project purpose is to use a documentary bibliographical review in order to analyze the factors that influence pre-writing in 5-year-old boys and girls to promote the psychomotor development in initial education at ''Belisario Quevedo'' Educational Unit The goal research is to diagnose the prewriting in children from 4 to 5 years old to promote their psychomotor development, and with the help of Early Education teachers, strengthen motor development and define the pre-writing difficulties. The approach was qualitative and the survey technique to data collection. It had 8 open questions asked to the teachers of the institution. Also, the observation was applied to initial education children. It determined that there is an average percentage where children do not develop their fine motor skills in correct way. This shortage provokes a lot of difficulties to carry out motor activities in the classroom. This multifactorial problem has a short-term solution with adequate guidance from their teacher through different playful activities for their improvement. The different theories and authors concluded that children from 18 months of age manipulate objects as an initiation to pre-writing. For this reason, the children should be stimulated from an early age. It is the basis for their effective development in school. Therefore, it allows the child to get abilities and skills that strengthen their learning